Study Filter Materials for Vertical Subsurface Flow Constructed Wetland to Treat Wastewater from the Da Mai Noodle Handicraft Village in Bac Giang Province - Van Thanh, Nguyen; Kim Anh, Bui Thi; Thu Thuy, Nguyen Thi; Hong Yen, Nguyen; Hong Chuyen, Nguyen; Dinh Kim, Dang (VNU Journal of Science: Earth and Environmental Sciences, 2024)
Vertical subsurface flow-constructed wetlands (VSF CW) are evaluated in this research as a potentially effective and cost-efficient solution for treating wastewater from Da Mai noodle handicraft village in Bac Giang province. Due to the high pollution load in this type of wastewater, there are concerns about clogging and the stability of the technology. In this study, we explored different sizes of limestone and gravel for the five medium composition formulas in the VSF CW system. The experiments were conducted over a period of three months. We used ANOVA, one-sample T-test, and Pearson correlation analysis methods to evaluate the experimental results, with statistical significance set at 0.05. The results showed a linear correlation between medium size, hydraulic conductivity, and treatment efficiency (p < 0.05). Smaller medium sizes had higher pollutant removal efficiency but lower porosity and hydraulic conductivity. For the same sizes, limestone demonstrated higher treatment efficiency compared to gravel (p < 0.05). The Cp5 formula (comprising sand, 1 × 2 cm limestone, and 3 × 5 cm gravel) was selected as the best filter medium for VSF CW, achieving COD, TSS, TN, and TP removal efficiencies of 86.02 ± 1.71%, 81.15 ± 2.24%, 64.46 ± 2.23%, and 69.76 ± 2.68%, respectively. After three months of operation, the treated wastewater consistently met QCVN 40:2011/BTNMT Column B standards, and there were no significant differences in hydraulic conductivity (p > 0.05), indicating stable operation of the VSF CW.